2015
DOI: 10.1186/1471-2288-15-2
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for recruitment and factors associated with motivation and satisfaction in a randomized trial with 210 healthy volunteers without financial compensation

Abstract: BackgroundThe aim was to describe a strategy for recruitment of healthy volunteers (HV) to a randomized trial that assessed the efficacy of different telephone techniques to assist HV in performing cardiac massage for vital emergency. Participation in the randomized trial was not financially compensated, however HV were offered emergency first-aid training. We also studied factors associated with HV motivation and satisfaction regarding participation in the trial.MethodsStrategy for recruitment of 210 HV aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
(42 reference statements)
1
12
0
Order By: Relevance
“…Given that over half of the participants in the current study (n=17) were university students or had completed tertiary education, their desire to learn may be a greater motivating factor than those without a tertiary education. Previous quantitative studies have similarly found that the opportunity to learn was an important motivator36 as well as the opportunity for expanded social contact 21…”
Section: Discussionmentioning
confidence: 95%
“…Given that over half of the participants in the current study (n=17) were university students or had completed tertiary education, their desire to learn may be a greater motivating factor than those without a tertiary education. Previous quantitative studies have similarly found that the opportunity to learn was an important motivator36 as well as the opportunity for expanded social contact 21…”
Section: Discussionmentioning
confidence: 95%
“…We could find only one previous study that described strategies for recruiting healthy volunteers [20], which compared 2 methods to find volunteers to test a telephone-based education program in emergency Figure 1. Top: percent of subjects who responded to the follow-up survey who ranked the listed method as their first or second choice to be contacted about research studies.…”
Section: Discussionmentioning
confidence: 99%
“…We could find only one previous study that described strategies for recruiting healthy volunteers [20], which compared 2 methods to find volunteers to test a telephone-based education program in emergency cardiac massage: a previously developed healthy volunteer database Versus posters and media advertisements aimed at the general public. Ten percent of the subjects they called from their database enrolled in the study, while they had little success with posters and media advertisements.…”
Section: Discussionmentioning
confidence: 99%
“…Explainable variance for the prediction of job involvement from a combination of participation frequency, on-job training, achievement orientation and job satisfaction was 33.6% (Li, Lin, & Chen, 2007). Job satisfaction positively influenced intention and it acted as a full mediator in the relationship between intrinsic motivation and intention to continue volunteering (Luzurier, Damm, Lion, Pellerin, & Tavolacci, 2015). Bennett & Barkensjo (2005) found strong connection between job satisfaction and a volunteer's personal commitment to providing high-quality services in a helping and caring charitable organization.…”
Section: Introductionmentioning
confidence: 96%
“…However, turnover among volunteer presents a significant problem for nonprofits (Scherer, Allen & Harp, 2016). It seems crucial to provide volunteers not only with a direct interest but also to ensure their satisfaction in order to enhance their recruitment (Luzurier, Damm, Lion, Pellerin, & Tavolacci, 2015). Results showed that job satisfaction mediated the relationship between perceived investment in employee development and intention to stay for both volunteers and paid employees (Fallon & Rice, 2015).…”
Section: Introductionmentioning
confidence: 99%